Pengaruh Brand Awareness, Brand Association Dan Perceived Quality Terhadap Loyalitas Pelanggan Kecap Manis Merek Abc (Studi Konsumen Swalayan ADA Siliwangi Semarang) - Florentinus Hendi Hera Quantrianto Prihatin Tiyanto Priagung Hutomo Emiliana Sri Pujiarti (Untag Semarang, 2013)
ABSTRACT This study aimed to analyze the effect of brand awareness, brand Association and perceived quality on customer loyalty ABC soy sauce brand in ADA Siliwangi SemarangThe population is consumers who buy soy sauce at ABC Sports brand ADA Siliwangi Semarang where the amount is not known for certain. The number of samples taken will be rounded to 100 respondents by the method of sample collection is nonprobality sampling. The analysis tool used is multiple regression and hypothesis testing.Based on this study concluded that there is a positive and significant relationship between brand awareness to brand loyaltyABC sweet soy sauce (1) There is a positive and significant relationship between brand loyalty Association for ABC sweet soy sauce brand(2) there is positive and significant relationship between Perceived Quality on customer loyalty ABC sweet soy sauce brand (3) Keyword : Brand Awareness,Brand Association, Perceived Quality, Customer Loyalty ABSTRAK Tujuan penelitian ini adalah untuk menganalisis pengaruh Brand Awareness, Brand Association dan Perceived Quality terhadap Loyalitas Pelanggan kecap manis merek ABC di Swalayan ADA Siliwangi Semarang.Populasi penelitian adalah pelanggan yang membeli kecap kecap manis ABC di ADA Siliwangi Semarang, yang tidak diketahui jumlahnya secara pasti. Sampel terdiri dari 100 responden, yang diambil dengan menggunakan metode non-probabilitas sampling. Analasis data menggunakan Regresi berganda dan Uji Hipotesis.Hasil penelitian menyimpulkan bahwa Brand Awareness, Brand Loyalty, Perceived Quality berpengaruh positif dan signifikan terhadap Loyalitas Pelanggan Kata kunci : Brand Awareness, Brand Association, Perceived Quality, Loyalitas Pelanggan